Nurses' perspectives on the role of relatives in emergency situations in nursing homes: a qualitative study from Germany - Schwabe, Sven; Bleidorn, Jutta; Günther, Andreas; Primc, Nadia; Rubeis, Giovanni; Schneider, Nils; Poeck, Juliane (BMC geriatrics, 2022)
BACKGROUND: In nursing homes, emergencies often result in unnecessary hospital transfers, which may negatively affect residents' health. Emergency management in nursing homes is complicated by structural conditions, uncertainties and difficulties communicating with the treating healthcare professionals. The present study investigated the role played by relatives in this emergency management, as perceived by nursing staff. METHODS: Within the context of a larger multi-method, interdisciplinary research project, we conducted six focus group discussions and 33 semi-structured interviews with nurses at nursing homes in northern Germany between September 2020 and April 2021. Discussions and interviews focused on emergency management in nursing homes, and were recorded, transcribed and analysed using qualitative content analysis, according to Mayring. RESULTS: Nurses reported that relatives were actively involved in emergency management in the nursing homes. Relatives were informed when there was an emergency situation, and they participated in decision making around the resident's care. Nurses sometimes perceived the involvement of relatives as challenging, due to a lack of time or staff, the opposing views of relatives and/or uncertain communication structures; however, they were willing to involve relatives according to the relatives' preferences. The role played by relatives was seen to range from that of an active supporter to that of a troublemaker. On the one hand, relatives were reported to support nurses in emergency management (i.e. by identifying residents' preferences and advocating for residents' interests). On the other hand, relatives were often perceived by the nurses as overstrained and unprepared in emergency situations, leading them to override residents' wishes, question the emergency plan and put pressure on the nurses' decision making. CONCLUSIONS: Nurses perceive the roles played by relatives in emergency situations in nursing homes as relatively supportive or, alternatively, demanding and troublesome. The timely involvement of relatives in emergency planning, the establishment of clear agreements with general practitioners and the development of trusting relationships between nursing staff and relatives may improve emergency management for nurses.